IMPLEMENTASI MINDFULNESS PEDAGOGY DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN KONSENTRASI BELAJAR SISWA DI SMK ARYASATYA TEKNOLOGI PATIKRAJA BANYUMAS: The Implementation of Mindfulness Pedagogy in Islamic Religious Education Learning to Improve Students’ Learning Concentration at SMK Aryasatya Teknologi Patikraja Banyumas - Hanifatun Nafisah; Muh. Hanif (TA'LIMUNA: Jurnal Pendidikan Islam, 2026)
Low student concentration in the digital age poses a challenge for Islamic Religious Education (Pendidikan Agama Islam, PAI) instruction, particularly in vocational high schools (SMK), where distractions are high. This article analyzes the implementation of mindfulness pedagogy in PAI instruction and its contribution to improving 10th-grade students' concentration at Aryasatya Teknologi Patikraja Vocational High School (SMK) in Banyumas Regency, Central Java. This article employs a qualitative case study design. Primary data were collected through participant observation and in-depth interviews, while secondary data were gathered via documentation. The data were analyzed using the Miles and Huberman interactive model, and data validity was verified through triangulation. The study's results indicate that the implementation of mindfulness pedagogy in PAI instruction at SMK Aryasatya comprises three stages: mindful breathing, mindful listening, and contemplative reflection. The implementation of mindfulness pedagogy improved students’ mental readiness and attentional focus, while reducing distracting behaviors. The application of mindfulness pedagogy also transformed the classroom climate into a more conducive environment during PAI instruction. Rendahnya konsentrasi belajar siswa di era digital menjadi tantangan dalam pembelajaran Pendidikan Agama Islam (PAI), khususnya di Sekolah Menengah Kejuruan (SMK) dengan tingkat distraksi yang tinggi. Artikel ini bertujuan menganalisis implementasi mindfulness pedagogy dalam pembelajaran PAI serta kontribusinya terhadap peningkatan konsentrasi belajar siswa Kelas X di Sekolah Menengah Keatas (SMK) Aryasatya Teknologi Patikraja, Kabupaten Banyumas, Jawa Tengah. Artikel ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Data primer dikumpulkan melalui observasi partisipatif dan wawancara mendalam; sedangkan data sekunder melalui teknik dokumentasi. Lalu data dianalisis menggunakan model interaktif Miles dan Huberman, serta validitas data diperiksa dengan teknik triangulasi. Hasil penelitian menunjukkan bahwa implementasi mindfulness pedagogy dalam pembelajaran PAI di SMK Aryasatya terdiri dari tiga tahap, yaitu mindful breathing, mindful listening, dan refleksi kontemplatif. Implementasi mindfulness pedagogy mampu meningkatkan kesiapan mental, fokus perhatian, serta mengurangi perilaku distraktif siswa. Penerapan mindfulness pedagogy juga mengubah iklim kelas menjadi lebih kondusif selama pembelajaran PAI. Kata Kunci : Konsentrasi Belajar; Mindfulness Pedagogy; Pembelajaran PAI; Pendidikan Agama Islam.